2021
DOI: 10.32598/irj.20.specialissue.919.3
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Validity, and Reliability of the Upper Extremity Fugl-Meyer Assessment (FMA-UE) in Persian Speaking Stroke Patients

Abstract: Objectives: Fugl-Meyer Assessment (FMA) is the common scale for clinical and functional evaluation of sensorimotor conditions and related Upper Extremity (UE) dysfunction after stroke. This study was done to translate and cross-culturally adjust the original upper extremity FMA (FMA-UE) into Persian and to evaluate the psychometric properties of the translated version. Methods: A procedure of forward/backward translation based on the published guidelines was adopted and two independent bilingual translators p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The Fugl-Meyer Assessment of the Upper Limbs (FMA-U/L) was used to evaluate upper-limb functionality. The FMA-U/L score is a tool for evaluating the body’s structure, function, and activity level as an evaluation tool for evaluating motor function according to Brunnstrom’s recovery phase in Step 6 [ 23 ]. The FMA-U/L is the most commonly used evaluation tool for upper-limb evaluation and consists of the sum of shoulder/elbow movement and wrist/hand items [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Fugl-Meyer Assessment of the Upper Limbs (FMA-U/L) was used to evaluate upper-limb functionality. The FMA-U/L score is a tool for evaluating the body’s structure, function, and activity level as an evaluation tool for evaluating motor function according to Brunnstrom’s recovery phase in Step 6 [ 23 ]. The FMA-U/L is the most commonly used evaluation tool for upper-limb evaluation and consists of the sum of shoulder/elbow movement and wrist/hand items [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…For early post-stroke impairment investigation, assessment is mostly done pre-treatment, within treatment and after rehabilitation. A standardized globally usage of FMA-UE for comparison of hemiplegic or paraplegic recovery results in improving standards of treatment 9 . Team of Hira Rehman in 2022 conducted a randomized control trial to ascertain the results of cortical mapping in chronic stoke and observed combining action observation therapy with standard therapy an effective strategy for rehabilitating upper trunk or limb movement in patients 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This tool equally assesses upper (17) and lower limbs (18) by covering multiple domains like motor, sensation, balance, joint range of motion, and joint pain. The reliability (internal consistency) of FMA-UE was 0.86 (19) while that of FMA-LE was 0.935 (20). Furthermore, trunk control was assessed by EMG biofeedback (21) Muscle performance refers to a muscle's combined strength, power, rate of force development, endurance, as well as its overall capacity to carry out tasks.…”
mentioning
confidence: 99%